Use of a Modified Nance Appliance for Esthetic Rehabilitation of a Child Patient with Rare Nonfamilial and Nonsyndromic Oligodontia - Abbas O. Al-Ahmadi; Ali A. Assiry; Siraj D. A. A. Khan; Anand Marya; Adith Venugopal; Mohmed Isaqali Karobari (Case Reports in Dentistry)
Congenital absence of more than 6 teeth except the third molar is known as oligodontia. It can affect both primary and permanent dentitions. The affected individuals usually demonstrate esthetic, functional, and psychological concerns. The present case report is about a 4-year-old female patient with multiple missing (both primary and permanent) teeth with esthetic and social problems. On extraoral examination, the patient demonstrated upper lip relapse due to missing anterior teeth. On physical examination, no other abnormality was detected in relation to the hair, appendages, or presence of a cleft. On intraoral and radiographic examination, 21 teeth were missing, which included both the primary and the permanent tooth buds. To encourage a positive behavioral change, it was decided to carry out prosthetic intervention using a modified fixed Nance appliance and acrylic teeth. After the replacement of the missing teeth, a marked improvement in the profile and esthetics was seen.